Antiracism defined as equitable sociocultural interactions in prekindergarten: Classroom racial composition makes a difference. Issue 3 (3rd May 2022) - Curenton, Stephanie M.; Rochester, Shana E.; Sims, Jacqueline; Ibekwe‐Okafor, Nneka; Iruka, Iheoma U.; García‐Miranda, Arlene G.; Whittaker, Jessica
Abstract: This study used secondary data from the My Teaching Partner‐Math/Science 2013–2016 randomized control trial to explore whether equitable sociocultural classroom interactions (see Curenton et al., 2019) were associated with the skills of 105 four‐ and five‐year‐olds (52% boys; drawn from 20 unique video recordings of preschool teachers/classrooms; 43% were Black, Latine, Asian, or other racially marginalized learners). Equitable interactions predicted children's skills with effect sizes ranging from small (0.01–0.44) to large (1.00). Moderation analyses revealed that when classrooms had more racially marginalized learners, teachers' use of equitable disciplinary and personalized learning practices were associated with higher executive functioning gains across prekindergarten. Findings illustrate how classroom composition can be a key indicator between equitable classroom interactions and young children's early skills.